2016
DOI: 10.3906/zoo-1510-54
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity of brown trout Salmo trutta (L.) in the broader Iron Gate area

Abstract: Mitochondrial DNA (mtDNA) haplotypes of brown trout (Salmo trutta L.) populations in the area of Djerdap National Park were analyzed in order to determine their phylogeographic statuses. Sequencing the control region of mtDNA in 66 specimens from 9 streams in the broader Iron Gate area revealed that 7 brown trout from those streams carried haplotypes of Atlantic lineage, while the remaining 59 fish were of Danubian lineage, either of Da23c or Da1 haplotypes. Four streams were inhabited by populations of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In contrast to the positive effects that sustainable management in trout fisheries have [e.g., the conditional and unconditional catch-and-release (Simonović et al, 2018)], both fishery managers and trout farmers fostered stocking of farmed brown trout fry and even spent brood fish (Simonović et al, 2014) to quickly enhance brown trout fisheries and accelerate return of investments (Simonović et al, 2017b). Based on recent knowledge of the native diversity of brown trout in the Western Balkans (Marić et al, 2006;Simonović et al, 2017a) and the risks posed to them by the introduction of non-native strains of brown trout and related species might pose to them (Simonović et al, 2013(Simonović et al, , 2015, recent surveys have revealed the occurrence of permanent, long-lasting introduction caused by stocking streams attractive for trout fisheries (Simonović et al, 2014;Škraba Jurlina et al, 2018), streams originally devoid of trout prior to stocking (Jadan et al, 2007;Simonović et al, 2018), and even streams that are not at all suitable for brown trout fisheries (Tošić et al, 2016;Škraba et al, 2017). Introduction of trout fish of the non-native haplogroups and of the non-native haplotypes in the dispersal area of brown trout of the DA haplogroup in the Western Balkans has been a long-standing practice since the mid-nineteenth century at least, when Slovenia, Croatia, and Bosnia and Herzegovina were parts of the Austro-Hungarian Empire (Razpet et al, 2007;Simonović et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the positive effects that sustainable management in trout fisheries have [e.g., the conditional and unconditional catch-and-release (Simonović et al, 2018)], both fishery managers and trout farmers fostered stocking of farmed brown trout fry and even spent brood fish (Simonović et al, 2014) to quickly enhance brown trout fisheries and accelerate return of investments (Simonović et al, 2017b). Based on recent knowledge of the native diversity of brown trout in the Western Balkans (Marić et al, 2006;Simonović et al, 2017a) and the risks posed to them by the introduction of non-native strains of brown trout and related species might pose to them (Simonović et al, 2013(Simonović et al, , 2015, recent surveys have revealed the occurrence of permanent, long-lasting introduction caused by stocking streams attractive for trout fisheries (Simonović et al, 2014;Škraba Jurlina et al, 2018), streams originally devoid of trout prior to stocking (Jadan et al, 2007;Simonović et al, 2018), and even streams that are not at all suitable for brown trout fisheries (Tošić et al, 2016;Škraba et al, 2017). Introduction of trout fish of the non-native haplogroups and of the non-native haplotypes in the dispersal area of brown trout of the DA haplogroup in the Western Balkans has been a long-standing practice since the mid-nineteenth century at least, when Slovenia, Croatia, and Bosnia and Herzegovina were parts of the Austro-Hungarian Empire (Razpet et al, 2007;Simonović et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…In the inland waters of the Danube River catchment, reservoir-dwelling migrating trout were recorded soon after the construction of dams, though it is not yet known whether those individuals belong to native trout of the DA lineage or to introduced trout of the AT lineage or whether they are an admixture of both of them. The discovery of brown trout individuals in the Djerdap (Iron Gate) One reservoir and in the lowermost sections of streams draining into the Danube River there (Figure 1, localities 1-7) confirmed they belong to the AT lineage or are admixed with it (Marić et al, 2012;Simonović et al, 2015Simonović et al, , 2017aTošić et al, 2016). There are no records of these trout in the upstream, headwater sections, where pure brown trout of the very specific Da23c haplotype still occur (Tošić et al, 2016).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations